Foreign direct investment and gross domestic products growth in Sri Lanka: An autoregressive distributive lag bounds test approach - Tharsika, K. (University of Kelaniya, 2022)
In the middle of this year, a burning topic in Sri Lanka was the countrywide outbreak of protests, which the government is struggling to control. Sri Lanka's GDP growth is plummeting due to poor government policies and COVID-19 pandemic. As a result, the Sri Lankan government must devise a strategy to boost the country's GDP growth. Foreign Direct Investment (FDI) boosts the country's economic growth directly or indirectly, making it a vital tool for economic reform in this globalization era. FDI is particularly important in helping developing countries accelerate their GDP growth. However, empirical evidence on the links between FDI and GDP growth is mixed. As a result, this study aims to investigate the short and long-run relationship between FDI, net inflows (BoP, current million US dollars), and Sri Lankan GDP growth. The study used annual time series data from the World Bank and central bank annual reports from 1981 to 2020 to examine the research puzzle. The Augmented Dicky Fuller (ADF) unit root is used to investigate the stationarity properties of the two selected variables. The ADF unit root test results demonstrate that neither of the study variables of GDP and FDI is stationary at the 2nd difference. In addition, both variables are integrated in a mixed order of at level and 1st difference. The results support the eligibility of the ARDL model application for this study. The ARDL bounds test result concludes that there is a long-run relationship between the FDI and GDP growth in Sri Lanka. Further, the error correction model proves a short-run causality between selected variables. Thus, this study's findings show a short and long-run relationship between the variables studied. The results of this study provide implications to policymakers and governments in designing appropriate policies for encouraging FDI within countries, which indirectly boosts economic growth.
Keywords: Autoregressive distributive lag; Bounds test; Foreign direct investment; Gross domestic products growth; Unit root test